2018
DOI: 10.1017/s1092852918001190
|View full text |Cite
|
Sign up to set email alerts
|

Examining the validity of the ADHD concept in adults and older adults

Abstract: ObjectiveIt is crucial to clarify the structure of attention-deficit/hyperactivity disorder (ADHD) symptomatology in all age groups to determine how to best conceptualize this disorder across the lifespan. We tested the ADHD factor structure across adulthood and investigated independent associations with executive functions.MethodData from 645 adults aged 18–59 and 233 adults aged 60–85 were drawn from the Nathan Kline Institute Rockland Sample. Participants completed the Conners Adult ADHD Rating Scale and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Even young adults are poor historians of their childhood ADHD symptoms: nearly 40% of 22-year-old adults who do not recall their childhood symptoms actually did have ADHD as children, and roughly 60% remember symptoms that, in fact, were not present (Breda et al, 2020 ). A possible recall bias is supported by one study’s data (Walitza et al, 2007 ): healthy control participants (mean age 57.2 years) reported significantly fewer ADHD symptoms relative to the younger healthy normative sample (mean age 29.8 years: Retz-Junginger et al, 2002 ), whereas it has been established that population samples of younger and older adults should endorse similar rates of ADHD symptoms (Callahan and Plamondon, 2019 ). Self-report is also less sensitive than informant-report for detecting current and past ADHD symptoms (Zucker et al, 2002 ; Sibley et al, 2012 ).…”
Section: Critical Appraisal Of Methodological Approachesmentioning
confidence: 97%
“…Even young adults are poor historians of their childhood ADHD symptoms: nearly 40% of 22-year-old adults who do not recall their childhood symptoms actually did have ADHD as children, and roughly 60% remember symptoms that, in fact, were not present (Breda et al, 2020 ). A possible recall bias is supported by one study’s data (Walitza et al, 2007 ): healthy control participants (mean age 57.2 years) reported significantly fewer ADHD symptoms relative to the younger healthy normative sample (mean age 29.8 years: Retz-Junginger et al, 2002 ), whereas it has been established that population samples of younger and older adults should endorse similar rates of ADHD symptoms (Callahan and Plamondon, 2019 ). Self-report is also less sensitive than informant-report for detecting current and past ADHD symptoms (Zucker et al, 2002 ; Sibley et al, 2012 ).…”
Section: Critical Appraisal Of Methodological Approachesmentioning
confidence: 97%
“…The DLB inclusion criteria followed a similar template with specific changes relevant to the DLB topic: (1) Participants must be human and 40 years of age or older; (2) A formal diagnosis of DLB must be a part of the study, using any version of the McKeith criteria 17 or adjusted criteria if studying a prodromal/mild cognitive impairment phase; (3) Studies were excluded if the sample included participants with comorbid neurodegenerative disorders (eg, DLB with comorbid Alzheimer disease); some studies reported depressive symptomatology in their DLB samples and those studies were retained; (4) Studies that included participants with Parkinson disease were excluded; (5) The study must include a clinical cognitive measure (ie, experimental measures were excluded); (6) DLB data must be reported in comparison to a control group, or report standardized scores calculated using normative data; (7) The neurocognitive measures are not used exclusively for correlational purposes or as predictors of a noncognitive outcome (eg, cognition as a predictor of survival); (8) Participants are generally considered representative of broader real-world samples (eg, samples consisting exclusively of veterans were excluded). These criteria were chosen to limit the included literature to clinically relevant findings, since the goal of the systematic review was to inform clinical decision-making.…”
Section: Study Selectionmentioning
confidence: 99%
“…Attention-deficit/hyperactivity disorder (ADHD) is generally considered a disorder of childhood, but there is growing recognition that symptoms can persist well into adulthood and late life. [1][2][3] Evidence suggests that behavioral (hyperactive) symptoms wane with age and give way to predominantly cognitive (inattentive) symptoms, 1,2,4,5 which may manifest as absentmindedness and forgetfulness. 6 In older adults, these symptoms can be misrecognized as signs of early dementia and contribute to misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its cognitive features (inattention, distractibility, impulsivity) tend to be associated with disruptions in executive functions (i.e., complex regulatory processes controlled in part by the frontal lobes) 3 , 4 . For example, increased ADHD symptoms in older adults, assessed as a continuous variable using the Conners Adult ADHD Rating Scale, have been linked to lower performance on tasks of working memory 5 and retrieval 6 , as well as slowed reaction time 6 . This aligns with findings of compromised frontal lobe integrity in ADHD 7 which, in older adults, may be compounded by the known deleterious effects of aging on frontal brain regions and processes 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%